Coupled effects of wind‐storms and drought on tree mortality across 115 forest stands from the Western Alps and the Jura mountains. (6th July 2017) - Csilléry, Katalin; Kunstler, Georges; Courbaud, Benoît; Allard, Denis; Lassègues, Pierre; Haslinger, Klaus; Gardiner, Barry
Abstract: Damage due to wind‐storms and droughts is increasing in many temperate forests, yet little is known about the long‐term roles of these key climatic factors in forest dynamics and in the carbon budget. The objective of this study was to estimate individual and coupled effects of droughts and wind‐storms on adult tree mortality across a 31‐year period in 115 managed, mixed coniferous forest stands from the Western Alps and the Jura mountains. For each stand, yearly mortality was inferred from management records, yearly drought from interpolated fields of monthly temperature, precipitation and soil water holding capacity, and wind‐storms from interpolated fields of daily maximum wind speed. We performed a thorough model selection based on a leave‐one‐out cross‐validation of the time series. We compared different critical wind speeds (CWSs) for damage, wind‐storm, and stand variables and statistical models. We found that a model including stand characteristics, drought, and storm strength using a CWS of 25 ms −1 performed the best across most stands. Using this best model, we found that drought increased damage risk only in the most southerly forests, and its effect is generally maintained for up to 2 years. Storm strength increased damage risk in all forests in a relatively uniform way. In some stands, we found positive interaction between drought and storm strength most likely because drought weakens trees, and they became more prone to stem breakage under wind‐loading. In other stands, we found negative interaction between drought and storm strength, where excessive rain likely leads to soil water saturation making trees more susceptible to overturning in a wind‐storm. Our results stress that temporal data are essential to make valid inferences about ecological impacts of disturbance events, and that making inferences about disturbance agents separately can be of limited validity. Under projected future climatic conditions, the direction and strength of these ecological interactions could also change. Abstract : We investigated the role of droughts and wind‐storms on adult tree mortality using 31‐year long time series from 115 stands in managed coniferous mountain forests from the Western Alps and the Jura mountains. We found that drought increased damage in the most southerly forests, and storms increased damage in all forests when the wind speed was higher than 25 ms −1 . Our data also suggest that drought may weakens trees, so that they became more prone to breakage under wind‐loading, but excessive rain may also lead to soil water saturation, which make trees more susceptible to overturning in a wind‐storm.